Is the volume of domestic patenting in Vietnam a cause for concern? An exploration of the issue and its policy implications - Thuong, Luong Van; Bo (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
This paper examines the assumption that the volume of domestic patenting in Vietnam is too low and needs to be expanded. The structure and state of development of the Vietnamese economy and a set of relevant systems - including the Science and Technology (S&T) System, the Intellectual Property System, the National Innovation System (NIS), and the Science, Technology and Innovation (STI) Policy System of Vietnam - are described and analyzed in order to determine, in qualitative terms, the extent to which the volume of domestic patenting is dependent on these framework conditions. An appraisal of the volume of domestic patenting is also been undertaken by analyzing data collected from various sources. The study concludes that Vietnam does not need to make a strong effort to increase the volume of domestic patenting per se. Instead, S&T, Intellectual Property Right (IPR) and STI policy systems should be strengthened to identify, develop and disseminate technologies appropriate for meeting the developmental goals. If these measures are effectively implemented, the NIS as a whole will also be strengthened and the industrialization of the country promoted. A system of technological indicators, including patent indicators, should also be established as a foundation for monitoring and analysing inventive and innovative activities. Keywords: Intellectual Property; Patents. Code: 14032704